No Evidence for the Actions of ’Clonidine-Displacing Substance’ on Alpha2-Adrenoceptors - Pinthong, Darawan (Journal of Basic and Applied Pharmacology, 2015)
It has been suggested that ’clonidine-displacing substance’ (CDS) is a putative endogenous substance at imidazoline receptor. CDS was found to recognize not only the imidazoline binding sites but also a2-adrenoceptors. However, the information of the functional activities of CDS at the a2-adrenoceptor is still limited. The aim of this study was to examine the properties and functions of CDS, in particular, the actions at a2-adrenoceptor. In the present study, the methanolic CDS extracts were prepared from bovine brain. CDS activity was determined by the amount of the extract that displaced 50% of [3H]-clonidine binding to bovine cerebral cortex membranes. CDS activity from bovine brain methanolic extract was 4.8±0.5 units/g wet weight. Based on radioligand binding assays, this extract recognized both a2-adrenoceptor on bovine cerebral cortex membranes labeled by [3H]-clonidine and non-adrenoceptor imidazoline binding sites on porcine renal cortex membranes labeled by [3H]-idazoxan. The CDS extract was found to be slightly more potent (2 folds) at a2-adrenoceptor than at non-adrenoceptor imidazoline binding sites. Functional studies of CDS were examined in the models of a,-adrenoceptor-mediated inhibition of forskolin-stimulated cAMP accumulation in guineapig cerebral cortex slices and in porcine isolated palmar lateral vein. The effects were compared to those of the known a,-adrenoceptor agonists, UK14304 and antagonized by the a2-adrenoceptor antagonist, idazoxan. The results from this study showed that bovine brain methanolic CDS extract did not display any activity involving a,-adrenoceptors as predicted from radioligand binding. In conclusion, CDS is able to displace clonidine from a2-adrenoceptor but no related biological activity was detected at this sites. Whether the possibility that CDS is an endogenous ligand at a2-adrenoceptor and at non-adrenoceptor imidazoline binding sites and possesses any significant activities at these sites remain to be clarified.